نحو النص: بين النظرية والإجراء - الزهرة يعقوب (Université de M'sila, 2019)
الملخص: حظي مصطلح "النص" بعناية خاصة في الدراسات اللغوية المعاصرة خاصة مع نشوء ما يعرف بـ"علم النص"و"لسانيات النص"و"نحو النص" ،ورغم الاختلاف الكبير بين علماء النصية في تحديد مفهومه،حيث اكتسى دلالات مختلفة نتيجة تعددا لاتجاهات والنظريات ، إلا انّه يمكن اعتباره وحدة أو تشكيل نظمي قابل للتحليل وكشف تماسكه. أفرز مفاهيم وتوجهات جديدة كانت لبنة للانتقال من الدراسة الجزئية الى الدراسة الشمولية وتجاوز نحو الجملة الى نحو النص. Abstract: The term ' text ' has received special attention in contemporary linguistic studies, , especially with the emergence of what is known as Text science ' and ' text Linguistics ' and ' Grammar the text', despite the significant difference between Towards the text Textual Scientists, which has acquired different connotations as a result of the multiplicity of trends and theories, , But it can be considered as a unit or a systemic formation can be analyzed and detected coherence. It produced new concepts and trends that were a building block for the transition from the partial study to the comprehensive study and to move towards the sentence towards theGrammar text
Keywords: الكلمات المفتاحية: النص؛الاتساق؛الانسجام؛نحو النص. ; text؛ coherence؛ harmony؛ Grammar the text